2021
DOI: 10.1093/ageing/afab054
|View full text |Cite
|
Sign up to set email alerts
|

Mass testing after a single suspected or confirmed case of COVID-19 in London care homes, April–May 2020: implications for policy and practice

Abstract: Introduction: Previous investigations have identified high rates of SARS-CoV-2 infection among residents and staff in care homes reporting an outbreak of COVID-19. We investigated care homes reporting a single suspected or confirmed case to assess whether early mass testing might reduce risk of transmission during the peak of the pandemic in London. Methods: Between 18–27 April 2020, residents and staff in care homes reporting a single case of COVID-19 to Public Health England had a nasal swab t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Furthermore, nursing homes with open-layout designs and large rooms divided into smaller individual rooms by use of wooden screens may have contributed to outbreaks in Hong Kong nursing homes due to inadequate ventilation. In these homes, four-foot high wooden screens were used to divide whole floors into numerous single-person bedspaces [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, nursing homes with open-layout designs and large rooms divided into smaller individual rooms by use of wooden screens may have contributed to outbreaks in Hong Kong nursing homes due to inadequate ventilation. In these homes, four-foot high wooden screens were used to divide whole floors into numerous single-person bedspaces [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some countries, the previous occurrence of other viral epidemics (e.g. SARS-CoV, MERS-CoV, H1N1) meant that there was a degree of understanding and preparedness surrounding mitigation of transmission in relation to PPE and sanitation [ 23 ]. However, for nursing homes in many other countries, COVID-19 represented their first learning curve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that once SARS-CoV-2 infection is introduced into an LTCF, it is difficult to limit transmission despite implementation of robust control measures. 13 14 Given these challenges, key preventive measures include ensuring high vaccination uptake for residents and staff, including booster doses for waning immunity and maintenance of good infection control measures to prevent introduction and transmission of SARS-CoV-2. 15…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, residents of LTCFs are less likely to be able to minimise their exposure to infectious persons because they are likely to be regularly exposed to staff providing care and may require more frequent contact with healthcare professionals due to medical needs. Studies have shown that once SARS-CoV-2 infection is introduced into an LTCF, it is difficult to limit transmission despite implementation of robust control measures 13 14. Given these challenges, key preventive measures include ensuring high vaccination uptake for residents and staff, including booster doses for waning immunity and maintenance of good infection control measures to prevent introduction and transmission of SARS-CoV-2 15…”
Section: Discussionmentioning
confidence: 99%